Evaluation of Toxicity and Antimicrobial Activity of Watery and Alcoholic extracts of some plant on growth of pathogenicBacteria isolatedfrom diarrhea - Al- Naemi, Hanan Adnan Shaker (The Iraqi Journal of Veterinary Medicine, 2012)
In This study, the bacteria Escherichia Coli, Salmonella typhimurium and Shigella dysentarea were isolated from diarrhea in infants. Microbiological and biochemical tests were conducted to identify these bacteria. In the Identification of bacterial Species the API-System was used. Sensitivity test of bacterial isolates revealed high resistance to many Antibiolics like Ampicillin, Tetracycline, Ceftazidine, Cephalothin ,Vancomycin and Rifamipicin.The effects of extracts of (Citrus aurantifolia ,Zingiber offienals, Glycyrrhiza glabra, Pimpinellaanisum, Camellia ,sinessis Coffeiaarabica, Elattariacar domomum, Cumminum cumminum, Thymus vulgaris and Trigonella foenum geoecum in inhibiting bacteria isolated from diarrhea were studied , also indication of presence of chemical active components in extracts was observed . The Preliminary chemical tests revealed acidic PH of all extracts, and the best antibacterial was effect that of Citrus aurantifolie an lcoholic extract on growth of E.coli with inhibition zone diameter 47mm.